STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI PROFESIONALISME GURU DI SDN BOJONG RAWALUMBU I - Safitri, Alifia; Widiansyah, Apriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher professionalism is an essential factor in improving the quality of learning and requires effective principal leadership strategies. This study aims to describe the principal's leadership strategies in implementing teacher professionalism at SDN Bojong Rawalumbu I. This research employed a qualitative approach with a descriptive method. The research subjects consisted of the principal, three teachers, and three students. Data were collected through interviews, observations, and documentation, and then analyzed using the Miles, Huberman, and Saldana data analysis model. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings indicate that the principal's leadership strategies in implementing teacher professionalism were carried out through four main aspects: (1) teacher development planning based on needs identification and performance evaluation; (2) planned and continuous academic supervision; (3) professional development and mentoring through the Teacher Working Group (KKG), In-House Training (IHT), learning communities, webinars, and training programs; and (4) evaluation and follow-up of teacher development as the basis for designing teacher competency development programs. These leadership strategies contributed to improving teacher professionalism and the quality of learning at the school.